HARMONISASI TRADISI RUWATAN PRANIKAH DALAM PERSPEKTIF HUKUM KELUARGA ISLAM: STUDI KASUS MASYARAKAT KEBONSARI, KEBUMEN - Annisa Maulidiyah; Mahsun Mahfudz; Fitrohtul Khasanah (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The prenuptial ruwatan tradition is part of the Javanese cultural heritage that is still practiced in Kebonsari Village, Petanahan District, Kebumen Regency. However, this practice often sparks debates between cultural values and Islamic teachings. Some community members believe that without ruwatan, marriage may bring misfortune, while others argue that the tradition contains elements of superstition and contradicts the principle of monotheism (tauhid). This issue reflects the tension between cultural preservation and the application of Islamic family law. This study aims to examine the practice of prenuptial ruwatan and assess its compatibility with the principles of Islamic family law. The research employs a qualitative approach through observation, interviews with traditional leaders, religious scholars, engaged couples, local residents, and literature review. The findings show that ruwatan in Kebonsari is not considered a requirement for a valid marriage but rather a symbolic social and spiritual tradition, such as the siraman ritual, which symbolizes self-purification before entering marital life. Local religious figures emphasize that the practice is acceptable as long as it does not contain elements of shirk (polytheism). Therefore, the prenuptial ruwatan can be harmonized with Islamic family law through educational and contextual approaches.